2022
DOI: 10.3390/ijerph192013131
|View full text |Cite
|
Sign up to set email alerts
|

Flare-Ups in Crohn’s Disease: Influence of Stress and the External Locus of Control

Abstract: (1) Background: The aim of this study was to explore the role of perceived stress and the health locus of control in Crohn’s disease and their influence upon the development of flare-ups of this disease. (2) Methods: Stress and the external locus of control were evaluated in a sample of 64 Crohn’s patients (flare-up phase versus latency phase). The perceived stress scale (PSS-14) and the multidimensional health locus of control scale were the measurement instruments used. (3) Results: The results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…With respect to the conclusions of our previous research, as well as taking into account the results found regarding the locus of control and stress, it was confirmed that in latency-phase patients with a low external locus of control, both stress and the locus of control influenced the development of outbreaks so that the higher the levels of these two variables, the greater the probability of an outbreak occurring [ 3 , 39 ].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…With respect to the conclusions of our previous research, as well as taking into account the results found regarding the locus of control and stress, it was confirmed that in latency-phase patients with a low external locus of control, both stress and the locus of control influenced the development of outbreaks so that the higher the levels of these two variables, the greater the probability of an outbreak occurring [ 3 , 39 ].…”
Section: Introductionsupporting
confidence: 65%
“…This matter is related to learning about and handling the disease which, based on previous relapse situations, has led these patients to know the importance of controlling and managing their pathology to increase their possibilities of avoiding new flare-ups and hospital admittance. As regards latency-phase Crohn’s patients, our previous studies verified that when the external locus of control was low, this variable, together with stress, were variables that influenced the development of outbreaks [ 3 , 39 ]. Additionally, when patients’ efforts were directed at controlling the pathology following the recommended treatment such as diet, medication, habits and so forth the probability of experiencing a flare-up was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Other . Exacerbation of symptoms in CD is also influenced by strong stress and sleep disturbances, which have been observed during periods of recurrence ( Anthony Sofia et al., 2020 ; de Dios-Duarte et al., 2022 ).…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…Because of the decline in its BOLD signal, UC patients are less receptive to happy feelings, which may be linked to the disease's start. Later, the de Dios-Duarte used the Stroop color word interference task to carry out two stress-induced repetition tests in order to look at how CD patients get accustomed to stress (29). The insula, thalamus, cerebellum, and medial temporal lobe (which includes the amygdala and hippocampus) were shown to have aberrant neuronal activity patterns in CD patients.…”
Section: Task-based Fmrimentioning
confidence: 99%